2017
DOI: 10.1002/aet2.10007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the R2D2 protocol: A Novel Method for Assessing Emergency Department Disposition for Residents

Abstract: Background: The emergency department (ED) disposition and discharge process is a critical period in a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…High patient turnout in surgery and emergency department, time spent operation theatres, patients care and other academic activities also found to be a contributing factor. A previous study applying this protocol in ED disposition found out that trained interns get better understanding of this discharge process leading to better patient care [5] . The results of that study were crucial as trained interns can handle this discharge and follow-up better after exposure to this R2D2 protocol.…”
Section: Introductionmentioning
confidence: 99%
“…High patient turnout in surgery and emergency department, time spent operation theatres, patients care and other academic activities also found to be a contributing factor. A previous study applying this protocol in ED disposition found out that trained interns get better understanding of this discharge process leading to better patient care [5] . The results of that study were crucial as trained interns can handle this discharge and follow-up better after exposure to this R2D2 protocol.…”
Section: Introductionmentioning
confidence: 99%